Design, synthesis, and progress of covalent organic frameworks (COFs)-based electrocatalysts for valorisation of biomass-derived platform chemicals - Changyu Weng; Hongmei Yuan; Lungang Chen; Xinghua Zhang; Qi Zhang; Longlong Ma; Jianguo Liu (Materials Today Advances, 2024)
The heavy reliance on fossil-based industries for basic chemicals not only contributes to severe global environmental problems but also hampers the sustainable development of the whole society. In addressing this issue, electrocatalysis utilizing biomass-derived platform chemicals provides a promising solution for the directed preparation of high-value chemicals. Among the various electrocatalysts, the remarkable appeal of COFs-based electrocatalysts has engendered great enthusiasm among researchers over the past decade due to the well-defined structure and large surface area of COFs. In this focused review, we highlight vital perspectives on the design, synthesis, and progress of COFs-based electrocatalysts in the electrocatalytic upgrading of biomass-derived platform chemicals. We provide a rational design of COFs-based electrocatalysts by incorporating metal species into the COFs frameworks and then regulate the local coordination environment and microstructure to facilitate efficient access to active centers, mass transportation, and electron transfer. This review offers a comprehensive understanding of the design principles underlying COFs-based electrocatalysts for platform molecules and its derivatives. Specifically, we thoroughly investigate the relationship between structure and performance, as well as synergistic effects within COFs-based electrocatalysts, aiming to shed light on the future design of next-generation electrocatalysts.